Влияние пространственных ограничений на микрофазовое разделение в последовательных полу-ВПС - Игнатова, Т.Д.; Алексеева, Т.Т.; Липатов, Ю.С.; Сорочинская, Л.А. (Видавничий дім "Академперіодика" НАН України, 2007)
Effect of the cross-link density of a polyurethane (PU) network on the phase separation that proceeds in the course of styrene polymerization in the swelling PU network has been studied. It is shown that an increase of the cross-link density of PU leads to an acceleration of phase separation. Phase separation in the early stage proceeds according to the spinodal mechanism.